2021
DOI: 10.1080/09638288.2021.1923838
|View full text |Cite
|
Sign up to set email alerts
|

Socio-environmental predictive factors for discharge destination after inpatient rehabilitation in patients with stroke: a systematic review and meta-analysis

Abstract: Purpose: To identify which of the socio-environmental factors of patients with stroke are predictive for discharge to their home after inpatient rehabilitation. Because discharge planning is a key component of rehabilitation, it is important to recognize the predictive factors for a discharge home. Other systematic reviews demonstrated the value of functional outcome measures. This review adds to the current literature by assessing the predictive value of socio-environmental factors, which shape the context in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…In addition, further studies are required to consider socio-environmental factors such as the presence of support at home, living with others, and marital status. These factors were reported as crucial for the consideration of home discharge in a previous systematic review 27) and in another Japanese study. 28) The paragraphs below include suggestions for the selection of treatment regimens based on the latent ADL status and patient subgroups according to ADL status at admission.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, further studies are required to consider socio-environmental factors such as the presence of support at home, living with others, and marital status. These factors were reported as crucial for the consideration of home discharge in a previous systematic review 27) and in another Japanese study. 28) The paragraphs below include suggestions for the selection of treatment regimens based on the latent ADL status and patient subgroups according to ADL status at admission.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have investigated the relationship between discharge home and the availability of a caring spouse or other person at home. 13,22,23 Similarly, the presence of a caregiver at home was associated with increased discharge to home, although Dutrieux et al 22 found this effect only in the patient group aged 70 years and above. Furthermore, living in an institution or at home with external help before stroke was a significant predictor of discharge to a residential facility.…”
Section: Discussionmentioning
confidence: 99%
“…In another review, support at home, living with others, being married, and living at home before stroke onset indicated a greater likelihood of a discharge home. 13 Moreover, while the impact of age and sex was less clear, a better pre-stroke functional and post-stroke cognitive status increased the likelihood of being discharged home. 14 In conclusion, different reviews recommend further research on age, sex, type of stroke, patient-specific biopsychosocial factors, other stroke-specific outcome measures, and global socioenvironmental determinants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations